Radiation losses of electron energy in multilayer bimetallic media - Borts, B.V.; Tkachenko, I.V.; Tkachenko, V.I. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Evaluation of radiation losses of the electron in inhomogeneous media is presented. Such media may appear as a composition of material layers with different dielectric constants or it may be modeled with the materials which dielectric permeability varies in the space. It is shown that in inhomogeneous media with dielectric permeability variable by harmonic law in space, the radiation losses of electron are proportional to square of parameter of inhomogeneity, that is are low. It is shown that in the inhomogeneous media with dielectric permeability varying in the space under the harmonic law, the radiation losses of the electron are proportional to square of the parameter of inhomogeneity i.e. are low. In the case when the conditions of parametric relation between eigen waves of the medium are satisfied radiation losses of electron are proportional to the parameter of inhomogeneity and are comparable to the losses during the acts of scattering.